Structural Analysis of Gol A Gong's Pucuk Dicinta Ulam Novel Arrives - Santi Tiur Minar Simamora; Harlen Simanjuntak; Elza L.L Saragih (Institut Agama Islam Negeri Palopo, 2023)
Literary vocabulary has often been heard by all levels of society, this is because literature has always existed in the midst of society because literature has been attached to daily activities and as an object of literature. The purpose of this study is to describe the structural elements and values contained in the novel